Analysis of Clove Agroforestry Productivity and Sustainability Using a Systemic Approach (MDS RAP-AFS) in Wolo District, Kolaka Regency - Andi Apriani Silondae; Sitti Rosmalah; Hartati Hartati; Adlina Husni Putri (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Kolaka Regency makes a significant contribution to clove production in Southeast Sulawesi. Wolo District, as one of the centers of clove production in Kolaka, faces complex challenges, including declining productivity. Agroforestry systems are expected to be a solution to increase productivity and the sustainability of clove farming in Wolo District. The purpose of this study is to analyze the productivity and sustainability of agroforestry-based clove farming. The method used to address the problem is productivity analysis and MDS analysis, utilizing the RAP-AFS approach (encompassing ecological, economic, social, and institutional dimensions). The results of the study show that clove productivity before the introduction of agroforestry in 2020 was 0.27 ton/ha. After the introduction of clove agroforestry in 2023, clove productivity began to increase, reaching 0.54 ton/ha in 2025. The level of sustainability of agroforestry-based clove farming in Wolo District, Kolaka Regency, is entirely in the fairly sustainable category in each dimension. The respective index values are ecological (67.01), economic (56.73), social (57.63) and institutional (51.90). The study's conclusion reveals that productivity has increased following the introduction of agroforestry, and the sustainability status of clove agroforestry in Wolo District, Kolaka Regency, is categorized as fairly sustainable, with the institutional dimension attribute being the most influential factor.